Three-dimensional ultrasound in the management of bladder endometriosis - Thonnon, Cyrielle; Philip, Charles-André; Fassi-Fehri, Hakim; Bisch, Christian; Coulon, Agnès; de Saint-Hilaire, Pierre; Dubernard, Gil (Journal of minimally invasive gynecology, 2015)
To assess the performance of three-dimensional (3D) ultrasound with color Doppler in the diagnosis of bladder endometriosis compared with magnetic resonance imaging (MRI) and cystoscopy. Canadian Task Force classification II-3. Department of gynecology and obstetrics of a university hospital. Eight women who reported urinary tract symptoms suggestive of bladder endometriosis between May 2012 and November 2013. For all cases, we assessed the size of the endometriotic nodule, its location on the bladder wall, and the distance between the lesion and the ureteral meatus, with pelvic 3D ultrasound (full bladder), uro-MRI, and cystoscopy. The results were compared with the postoperative histopathologic findings. The pathology results differed from those produced by imaging by a mean ± SD of -3.5 ± 6.4 mm on transvaginal ultrasound (TVUS) and -5.75 ± 11.9 mm) for MRI. There was no significant difference between imaging and pathology findings (p = .20) or between the 2 imaging findings (TVUS and MRI) (p = .73). Results showed a trend toward better accuracy for 3D ultrasound than MRI with smaller SDs (p = .08). Cystoscopy and ultrasound were compared; however, without any tools to assess the distance in cystoscopy, no statistical result was possible. Ultrasound seems to be superior to cystoscopy and is at least as effective as MRI in diagnosing and planning the surgery for bladder endometriosis.